Design criteria for evaluation and levels of readiness to teachers training student profile (Pedagogy of Higher and Secondary Education, 2012)
Prigodiy M. Design criteria for evaluation and levels of readiness to teachers training student profile.The article describes the results of theoretical generalizations on the issue of justification criteria and levels of readiness assessment of future teachers for Special Education students.
Keywords: criterion; measure readiness for school education; a teacher of technology